Peningkatan Efikasi Diri dalam Management Emosional untuk Masyarakat dengan Diabetes Mellitus - Yuliana, Yuliana; Wantoro, Giat (Prosiding Seminar Kesehatan Nasional, 2023)
Diabetes is a serious non-communicable disease where insulin cannot be produced optimally by the pancreas (Safitri & Nurhayati, 2019). Diabetes is caused by glucose intolerance which is progressive and takes place slowly (years) which results in long-term complications such as eye disease, peripheral neuropathy, or peripheral vascular disease. This change has substantially caused various psychological responses in diabetics (Fisher at all 2020), psychological responses experienced by diabetics can be in the form of stress, depression and anxiety (Singhai at all 2020). Most people are familiar with the term emotion associated with anger and hate. A person with DM to avoid complications needs to learn self-management to prevent complications. Community service was carried out in the legok village area which is the location of PkM STIKBA Jambi partners, the implementing team provided spiritual mindfulness education to 11 participants to control emotions. The results of the independent healthy target test with a value of 1-10, the higher the score the better. It was found that (5) participants with a score of 5 included Confidence in being able to overcome anger and negative feelings as many as (4) participants and Confidence in being able to overcome sadness when in trouble as many as (1) participants